HUBUNGAN KARAKTERISTIK KELUARGA DENGAN TINGKAT ANSIETAS SAAT MENGHADAPI KEKAMBUHAN PASIEN GANGGUAN JIWA - Livana PH; Yulia Susanti; Dimas Eka Ardika Putra (Indonesian Journal for Health Sciences, 2018)
Clients mental disorder characterized by cycles of recurrence, which reached 60-75% of all patients. Recurrence trigger psychological conflict such as anxiety in the family. Family characteristics need to be considered in understanding the problems of family anxiety when clients have a relapse. The purpose of this study was to determine the characteristics of a family relationship with the level of anxiety when faced with a client recurrence of mental disorders in RSJD Amino Gondhohutomo Semarang. The study used a descriptive correlational design with cross sectional approach. Sample was taken by purposive sampling as many as 40 families were clients of mental disorder experience recurrence in emergency ward RSJD Amino Gondhohutomo Semarang. Research tool questionnaire characteristics and Hamilton Anxiety Rating Scale (Hars). Statistic test used Kendall's tau_b and Somers’d. The results showed no relationship between job characteristics (pvalue = 0.029), income (pvalue = 0.040), and the type of family (pvalue = 0.027) with the anxiety level families in the face of recurrence clients with mental disorders, while the educational characteristics (pvalue = 0.390), relationship status (pvalue = 0.587), stage of development of the family (pvalue = 0.482), and ethnic culture (pvalue = a) there is no relationship. Further research is expected researching family anxiety when faced with a recurrence client by using different methods and samples consisting of various ethnic cultures Abstrak Klien gangguan jiwa dicirikan dengan siklus kekambuhan yang mencapai 60-75% dari keseluruhan penderita. Kekambuhan memicu terjadinya konflik psikologi seperti ansietas pada keluarga. Karakteristik keluarga perlu dipertimbangkan dalam memahami permasalahan ansietas keluarga saat klien mengalami kekambuhan. Tujuan penelitian ini adalah mengetahui hubungan karakteristik keluarga dengan tingkat ansietas saat menghadapi kekambuhan klien gangguan jiwa di RSJD Amino Gondhohutomo Semarang. Penelitian menggunakan desain deskriptif korelasional dengan pendekatan cross sectional. Sampel diambil secara purposive sampling sebanyak 40 keluarga klien gangguan jiwa yang mengalami kekambuhan di IGD RSJD Amino Gondhohutomo Semarang. Alat penelitian menggunakan kuesioner karakteristik dan Hamilton Anxiety Rating Scale (HARS). Uji statistik menggunakan uji Kendall’s tau_b dan uji Somers’d. Hasil penelitian menunjukan ada hubungan antara karakteristik pekerjaan (pvalue=0,029), penghasilan (pvalue=0,040), dan tipe keluarga (pvalue=0,027) dengan dengan tingkat ansietas keluarga saat menghadapi kekambuhan klien gangguan jiwa, sedangkan karakteristik pendidikan (pvalue=0,390), status hubungan (pvalue=0,587), tahap perkembangan keluarga (pvalue=0,482), dan etnis budaya  (pvalue=a) tidak ada hubungan. Peneliti selanjutnya diharapkan meneliti ansietas keluarga saat menghadapi kekambuhan klien dengan menggunakan metode berbeda dan sampel yang terdiri dari berbagai etnis budaya.